Role of immunostimulants in the culture of decapod crustacean - Huynh, Minh Sang (Curtin University, 2010)
Increased concerns on antibiotics used in aquaculture have promoted research toward alternative products. Immunostimulants have been approved to be good alternatives for antibiotics used in the culture of many species. A series of experiments were conducted under laboratory conditions to investigate the roles of immunostimulants, beta glucan (BG) and mannan oligosaccharides (MOS) in the culture of marron (Cherax tenuimanus), tropical rock lobster (Panulirus ornatus) and yabbies (Cherax destructor).BG showed survival, physiological and immunological improvements in marron through dietary supplementary levels of 0.1 to 0.2%. Dietary MOS at 0.2 to 0.4% inclusion level improved survival, health status and immune system of marron. Similar improvements of dietary MOS were observed in yabbies and tropical rock lobster. In addition, the growth of yabbies and tropical rock lobster increased with MOS supplemented diets. Dietary MOS also benefited marron, tropical rock lobster and yabbies by enhancing the biological functions of their digestive system. Marron and lobster fed MOS diets revealed a healthier gut condition with improvement in morphological structure and microbiota structure. MOS also changed digestive enzyme activities of yabbies. Further, dietary MOS lowered mortality of marron and tropical rock lobster when they were infected with bacteria. The resistance ability of marron to environmental stressors such as NH3 and air exposure during live transportation was also enhanced in marron fed MOS. In addition, there were no adverse effects of BG and MOS on the performances of above crustaceans.The current research implies that MOS and BG could be the used as alternatives to antibiotics in crustacean cultured under laboratory environment. In order to attain the optimum benefits of MOS and BG dietary supplementation in the commercial production of crustaceans, however, further research is suggested.